PARALLEL SCRIPTING FOR APPLICATIONS AT THE PETASCALE AND BEYOND. - Wilde, Michael; Foster, Ian; Iskra, Kamil; Beckman, Pete; Zhao Zhang; Espinosa, Allan; Hategan, Mihael; Clifford, Ben; Raicu, Ioan (Computer (00189162), 2009)
The article focuses on computer parallel scripting for the rapid development of parallel applications in platforms from workstations to petascale supercomputers. The method reportedly enables users to apply parallel composition constructs to existing programs in sequence and is advantageous for parameter sweeps and ensemble studies. It is stated that parallel scripting also allows for the quick analysis of individual or collections of discrete files or database records.